(untitled) (Psychology Travelogs, 2024)
The article presents a study on determining the psychological conditions for the development of resilience of future border guards in the conditions of a higher military educational institution.Resilience is defined by the author as a psycho-social phenomenon that structurally consists of personal, interpersonal and social elements and is the result of various development processes over a long period of time. Resilience characterizes how much the psyche is capable of recovery after adverse circumstances, after experienced stress. Personal qualities are described that have an impact on the ability of the psyche to recover and change the attitude to stressful events: neuroticism, self-esteem and locus of control. The author draws attention to the similarities in the meaning of the concepts «stress resistance» and «resilience». Since stress theories are the basis for the study of stress resistance, the author considers them as a basis for the study of resilience.Among the factors of the professional activity of border guards officers, the following are mentioned: significant variability of official assignments, lack of time for their execution; the need to maintain discipline in everyday life, constant readiness for mobilization, dexterity and composure; limitation of personal time, systematic danger; psycho-emotional overload, stressful situations during service. Attention is drawn to the fact that at the higher military educational institution, future border guards are trained for various types of activities: manage the unit in peacetime and wartime conditions, carry out psychological work with personnel in the unit, conduct training of servicemen, regulate the psyche of servicemen in the interests of the service.The article analyzes the approaches of scientists to the definition of resilience. According to the results of this analysis, as well as taking into account the specifics of the professional activity of border guards, the psychological conditions for the development of resilience of future border guards in the conditions of a higher military educational institution were determined: development of cadets’ professional motivation for success through an optimistic thinking style; application by teachers of psychological mechanisms of formation of locus of control in cadets when solving educational and professional tasks creation of appropriate educational and methodological support for the educational process; formation of critical thinking of future border guards; active use of training technologies for extreme activities.